Tactical aspects of laparoscopic rectum resection - Chinelli, Javier; Rodríguez Temesio, Gustavo (Cirugía del Uruguay, 2020)
Introduction: Laparoscopy is currently the approach of choice for oncological resections of the colon and rectum, since it does not compromise their quality and offers the advantages of minimally invasive surgery. Description of contents: The main tactical aspects of the anterior resection of the rectum are described: patient positioning and surgical equipment, positioning of the trocars and technical steps. Medial dissection of the mesocolon identifying retroperitoneal structures, vascular control of the superior rectal artery and inferior mesenteric vein, lateral mobilization of the colon, meso-rectal dissection, distal rectal section, exteriorization and section of the piece, intracorporeal anastomosis, and drains. In all the steps emphasis is placed on the prophylaxis of accidents and / or intraoperative adverse events.